Pengawasan pendidikan di masa pascapandemi: Peran pengawas dalam memulihkan kualitas pembelajaran di Sekolah Dasar dan Menengah - Nabilah, Nur Rahma (Maliki Interdisciplinary Journal, 2025)
arning has shifted from face-to-face to distance learning. Following this change, many problems have arisen, including a decline in the quality of learning, a decline in literacy and numeracy levels, and limited access to technology. In this situation, especially in primary and secondary schools, educational supervision has a strategic role to play in ensuring that the quality of learning recovers. This article discusses post-pandemic educational supervision concepts, with an emphasis on adaptive, collaborative, digital, and data-driven concepts. In addition, it presents innovations in academic supervision through the use of technology, reflective supervision to improve teacher professionalism, and supervision in the context of blended learning. The analysis shows that the use of digital supervision, improving teacher capabilities, and the use of data can improve the quality of learning. However, in its implementation, there are obstacles such as infrastructure limitations, human resource shortages, administrative pressure, and fear of change. This article provides practical suggestions for improving technological infrastructure, innovation-centered supervision training, continuous evaluation, enhancing a culture of teacher cooperation, and developing more flexible policies. Therefore, post-pandemic education supervision should be viewed as a comprehensive effort to improve the quality of education in a sustainable manner, not merely an administrative task.